Role of Fuel on Cation Disorder in Magnesium Aluminate (MgAl2O4) Spinel Prepared by Combustion Synthesis. Issue 9 (19th June 2015) - Dwibedi, Debasmita; Avdeev, Maxim; Barpanda, Prabeer; Vanderah, T.
<x xml:space="preserve">Abstract</x> Magnesium aluminate spinel (MgAl2O4) forms an interesting system having tetrahedral and octahedral voids filled with near similar sized divalent Mg2+ and trivalent Al3+ cations. Structural disorder (e.g., Mg–Al antisite defects) can be tuned by synthetic conditions. This study reports the evolution of Mg/Al disorder in MgAl2O4 prepared by combustion synthesis using different types of fuels. The effect of nature of fuel and the final calcination temperature (600°C–900°C for 9 h) on degree of cation ordering has been investigated combining powder X‐ray (XRD) and neutron (NPD) diffraction. The results indicate very high degree of inversion in the samples crystallized at low annealing temperature, which on further annealing reduces toward the thermodynamically stable values. Raman spectroscopy, probing MgO4, and AlO4 tetrahedral bonds, confirmed the results at a local level.